Rv0500A: Linking Mycobacterium tuberculosis environmental response and division - Kevorkian, Yuzo. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Molecular Microbiology.; Advisor: Carol Kumamoto.; Committee: Ralph Isberg, and Linden Hu.; Keyword: Microbiology.